Determination of Risk Factors Influencing Psoriatic Arthritis Screening and Evaluation Questionnaire Scores in Palmoplantar Pustulosis: Post Hoc Analysis of EPPPIK Study - Byung Soo Kim; Seong Jin Jo; Dong Hyun Kim; Hee Joo Kim; Chul Hwan Bang; Bong Seok Shin; Joo-Heung Lee; Ju Hee Lee; Sung Eun Chang; Kyung-Eun Jung; Youngdoe Kim; Jihye An; et al. (Dermatology and Therapy)
Abstract Introduction Palmoplantar pustulosis (PPP) is a chronic inflammatory skin condition characterized by pustules on the palms and soles. Patients with PPP may be at an increased risk of developing psoriatic arthritis (PsA). The Psoriatic Arthritis Screening and Evaluation (PASE) questionnaire is a tool designed to screen for PsA in at-risk populations. The objective of this study was to identify potential risk factors influencing PASE scores in patients with PPP. Methods The EPPPIK study was a cross-sectional, multicenter, noninterventional study conducted at 20 sites in Korea, in which patients (≥ 19 years of age) with a confirmed PPP diagnosis were reviewed. In a post hoc analysis of EPPPIK data, PASE outcomes were evaluated for two groups of patients with PPP stratified on the basis of a cutoff score of 37 points. Results In total, 375 patients with PPP (mean age, 51.3 years; 38.9% male) were included. At enrollment, 175 (46.7%) patients had a PASE score ≥ 37, and 200 (53.3%) patients had a PASE score < 37. Significant differences between the groups were demonstrated for sex, age of menarche, presence of arthritis or psoriatic arthropathy, Physician’s Global Assessment score, Palmo-Plantar Pustulosis Area and Severity Index (PPPASI) score, and hand PPPASI score (p ≤ 0.05). Quality-of-life (QoL) measurements and patient-reported outcomes were significantly worse in patients with PASE ≥ 37 (p ≤ 0.05). Multivariable linear regression analysis revealed that a PASE score ≥ 37 was positively associated with female sex (β = 7.19; p < 0.001) and high hand PPPASI score (β = 0.22; p = 0.0243). Conclusions In patients with PPP, PASE score ≥ 37 correlated with increased presence of any arthritis or psoriatic arthropathy, more severe PPP, worse QoL outcomes, female sex, and higher hand PPPASI scores. Therefore, PASE may serve as a useful tool for initial screening and appropriate treatment selection, management, and ongoing monitoring of patients with PPP.